Guided participation in youth media practices - de la Fuente Prieto, Julián (2020)
Youth has to deal with some digital practices and develop media discourses on their own. Our study aims to deepen these concepts from the point of view of the guided participation, understood in this case as a collaborative process of media literacy based on culturally significant activities. Our data comes from a series of workshops that took place at the Telefonica Flagship Store (Madrid, Spain) with teens between eight and 14 years old. The evidence was collected by qualitative research techniques such as observation, conversation and descriptive analysis. The results give us some preliminary ideas for discussion: 1) social media practices enable youth to connect their online and offline activities with their interests; 2) the generation of collaborative learning scenarios based on the interaction between young people becomes a fundamental element of media literacy and 3) user-generated content emerges as an identity and habits depiction in media, especially among young people.